Literature Review: Vestibular Illusions in Combat Flight: Implications and Management - Anugrah Dwi Riski; Retno Wibawanti (Hanggong uju uihakoeji)
Vestibular illusion is a common problem in combat aviation, which can cause spatial disorientation (SD) and potentially result in fatal accidents. This article discusses several types of SD, such as type I, type II, and type III, along with their characteristics and implications. Vestibular illusions, such as somatogravic illusion, somatogyral illusion, leans, Coriolis illusion, and G-excess illusion, are also presented as factors that can influence pilot decisions during flight. It is important for military aviators to understand and recognise these vestibular illusions to maintain spatial orientation and prevent accidents. Effective management of vestibular illusions, including the Coriolis illusion, involves training, awareness and mitigation strategies, such as the use of technological simulations like virtual reality. This training helps aviators recognize and overcome vestibular illusions, thereby improving overall flight safety.